Unconscionable conduct in commercial transactions : global perspectives and applications - Wooler, Garth (Cambridge Scholars Publishing, 2018)
This book looks at the historical use of allegations of unconscionable conduct within the context of independent trade finance instruments, such as letters of credit and demand guarantees. It makes a detailed survey of the law of unconscionable conduct, the complexities of the doctrine of independence, and the circumstances where the former prevails to provide relief from abuse. It also completes a wide-ranging, sequential audit of the relevant case law in both Singapore and Australia where unconscionable conduct was alleged in independent instrument matters. The audit examines every case along.